2009
DOI: 10.1117/12.837137
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of alignment/overlay sampling and marker layout to improve overlay performance for double patterning technology

Abstract: Double patterning technology is capable of extending usability of immersion ArF systems for 32nm half-pitch node and below. However, overlay errors between the two patterning steps will directly contribute to critical dimension variation in a dual litho-etch process. The overlay errors need to be reduced significantly to meet the tight critical dimension uniformity requirement in the technology nodes. The present scanners are able to correct intra-and inter-field overlay errors that include not only linear ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…They are larger than the dedicated target because it depends on number of via and trench length. 30 Results of the correlation of SEM-OL at AEI and optical IBO are shown in Fig. 8.…”
Section: Dedicated Mark and Algorithm Of Sem-ol Metrologymentioning
confidence: 99%
See 1 more Smart Citation
“…They are larger than the dedicated target because it depends on number of via and trench length. 30 Results of the correlation of SEM-OL at AEI and optical IBO are shown in Fig. 8.…”
Section: Dedicated Mark and Algorithm Of Sem-ol Metrologymentioning
confidence: 99%
“…To improve residual error after correction, higher-order correction to compensate the nonlinear overlay errors, correction per exposure (CPE) to correct overlay errors in each individual field have been applied in addition to linear correction to correct the intrafield and interfield overlay errors. 29,30 For the overlay corrections, small OL mark has been needed to be laid out in large numbers within die.…”
Section: Introductionmentioning
confidence: 99%
“…For linear models it generally results in a uniform distribution, while for higher order polynomial models, it generally results in a nonuniform distribution in which denser sampling is performed at the edges of the wafers and fields. Geometrybased method generates the sampling layouts based on optimal geometric distributions, but risks missing the local wafer signature [51][52][53] .…”
Section: Sampling Scheme Optimization Algorithmmentioning
confidence: 99%
“…Besides this, the choice of the locations across the wafer can strongly influence the accuracy of the APC correction. In a previous study was shown that modeling with a limited number of fields can adequately describe a fullwafer overlay signature and the errors could be well corrected accordingly [2].…”
Section: Introductionmentioning
confidence: 99%